Transparent electrode materials for solar cells - Meiss, J; Uhrich, C; Fehse, K; Pfuetzner, S; Riede, M; Leo, K (Society of Photo-Optical Instrumentation Engineers, 2008)
Alternatives for replacing the expensive ITO are explored and Poly(ethylene dioxythiophene):polystyrene sulfonate (PEDOT:PSS) is introduced as one possibility. We present the first small-molecule organic solar cells employing only PEDOT:PSS as transparent electrode. Solar cells on glass and on flexible plastic foil were prepared, using a p-doped hole transporting material, zinc phthalocyanine (ZnPc) and C60 as donor-acceptor heterojunction, and an exciton blocking layer. Different methods to structure the PEDOT:PSS electrodes were investigated and are presented. As proof of principle, non-optimized prototype cells with efficiencies of over 0.7% on glass and 0.9% on flexible plastic foil substrate were obtained.